Co-modification method suitable for chromium-nickel cladding coating
By adding NH4Cl, Pt and Ti to the slurry of the chromium-nickel coated coating and using laser cladding technology, the problem of insufficient stability and oxidation resistance of the chromium-nickel coating in the high-temperature steam environment in the prior art is solved, and a significant improvement in oxidation corrosion resistance is achieved.
Patent Information
- Application Number
- CN202510163388.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-04-11
AI Technical Summary
In the prior art, Cr2O3 has poor stability in high-temperature steam environments, resulting in loosening and peeling of oxide films, and low Cr content in the alloy matrix, and the antioxidant performance decreases with the increase of service time, which cannot effectively solve the corrosion failure problem of the boiler outer wall in the sulfur-containing flue gas corrosion environment.
A co-modification method suitable for chromium-nickel cladding coating is adopted to improve the preparation of solid-phase cladding powder and liquid-phase binder by adding NH4Cl, Pt and Ti to the slurry components, and combined with laser cladding technology, a high-quality chromium-nickel cladding coating is prepared.
The coating's oxidation and corrosion resistance in a high-temperature water vapor environment has been significantly improved, and the oxidation and corrosion resistance of the base material has been increased by 19-78 times, ensuring the stability and bonding strength of the coating.
Smart Images

Figure CN119800352A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present disclosure belong to the technical field of material surface alloying and coating preparation, and specifically relate to a co-modification method suitable for chromium-nickel cladding coatings. Background Art
[0002] In the thermal power generation industry, pipe blockage and pipe burst accidents caused by scale problems in large aspect ratio flow parts have become common industry problems and technical pain points that restrict the safe production and operation of the entire energy equipment, causing huge losses. At present, the Xi'an Thermal Engineering Institute has adopted a method of preparing Cr coating to solve the problem of corrosion failure of the outer wall of the boiler in the corrosive environment of sulfur-containing flue gas, and has achieved remarkable results. However, the stability of Cr2O3 in steam above 600°C is poor, and the loose oxide film caused by volatile products will cause the oxide film to peel off; in addition, the Cr content in the alloy matrix is relatively low. With the increase of service time, when the Cr content required for the growth of the oxide film cannot be supplemented, the oxidation resistance of the alloy will also drop sharply. Therefore, it is of great practical significance to study and develop new corrosion-resistant and oxidation-resistant coatings suitable for the inner and outer wall surfaces of pipelines for boiler units. Summary of the invention
[0003] The embodiments of the present disclosure aim to solve at least one of the technical problems existing in the prior art and provide a co-modification method applicable to chromium-nickel cladding coatings. The method is applicable to austenitic steel and high-temperature alloy parts used in large boilers, oil and gas field transportation pipelines and other large aspect ratio and various complex shaped workpieces.
[0004] The embodiment of the present disclosure provides a co-modification method applicable to a chromium-nickel cladding coating, comprising the following steps:
[0005] Step 1, weigh and prepare solid-phase cladding powder and liquid-phase binder in proportion, and prepare cladding slurries of different proportions after stirring and ball milling for use;
[0006] Step 2: Clean and preheat the surface of the workpiece to be plated, then spray the cladding slurry evenly onto the workpiece surface, and dry and solidify after spraying;
[0007] Step 3: placing the workpiece after the spray coating is solidified in an inert atmosphere for laser cladding, obtaining a chromium cladding coating after cooling, and performing cladding residue treatment.
[0008] Optionally, in step 1, the infiltration source is Cr or Ni powder, the modifier is Pt or Ti powder, the activator is NH4Cl, and the binder is ethyl acetate;
[0009] The solid phase components are weighed by mass percentage, including 40%-70% Cr, 20%-50% Ni, 0%-5% Pt, 0%-5% Ti and 1%-5% NH4Cl, wherein the Cr, Ni, Pt and Ti powders are sieved through a 1000 mesh sieve, and the solid phase components are mixed by ball milling in a planetary ball mill at a ball milling speed of 350rpm-400rpm for 12h-24h;
[0010] The binder ethyl acetate is added to the uniformly mixed solid phase powder at a mass ratio of 10%-30% of the solid phase component, and after being fully stirred for 2h-4h, it is placed in a planetary ball mill for ball milling mixing. The ball milling speed is 350rpm-400rpm and the time is 8h-12h.
[0011] Optionally, in step 2, the workpiece surface is pretreated by using a high-pressure water gun for cleaning and rinsing with alcohol or acetone; the preheating treatment is medium frequency preheating at 200°C-250°C for 30min-60min;
[0012] The thickness of the pre-sprayed layer is 1mm-5mm, and the coating coverage is not less than 98%;
[0013] The coating is dried by natural air drying for 24h-48h, and the curing treatment is cured at 300℃-450℃ for 24h-48h.
[0014] Optionally, in step 3, the laser power is 2KW-2.8KW, the scanning rate is 20mm / s-40mm / s, the spot diameter is 3mm-5mm, the workpiece rotation speed is 3r / min-6r / min, and the Ar gas flow rate is 15L / min-20L / min;
[0015] The residue is treated by flushing with a high-pressure water gun or high-pressure air flow and then naturally dried.
[0016] Compared with the prior art, the co-modification method for chromium-nickel cladding coating according to the embodiment of the present disclosure also has at least the following beneficial effects:
[0017] 1. By adding halide NH4Cl to the slurry components, it has the effect of promoting penetration and activation, and improves the penetration rate and coating quality;
[0018] 2. By adding modified elements Pt and Ti to the cladding powder components, the diffusion of parent material elements is inhibited and the corrosion resistance is enhanced;
[0019] 3. The coating is prepared by laser cladding process, which has concentrated heat, short action time, small thermal impact in the cladding area, and high bonding strength between the coating and the base material;
[0020] 4. The coating is prepared through an integrated laser cladding process production line. The coating has high production efficiency, controllable thickness, high process repeatability, and is extremely practical and universal.
[0021] Furthermore, the introduction of Pt element can inhibit the outward diffusion of alloy base material elements and improve the adhesion between the oxide film and the base material; the introduction of Ti element can produce fine-grained corrosion products to enhance the "stickiness" of the oxide film. The two can simultaneously inhibit internal sulfidation and oxidation.
[0022] Furthermore, the segmented slurry curing process of natural air drying combined with medium and low temperature curing effectively avoids the problem of micro cracks and tiny holes in the slurry layer caused by thermal stress during direct drying, and enhances the bonding strength between the slurry layer and the workpiece surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram of the cross-sectional morphology of the chromium-nickel cladding coating in Example 1 of the present disclosure. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.
[0025] A co-modification method for chromium-nickel cladding coating comprises the following steps:
[0026] Step 1. Weigh the solid phase components according to the mass ratio, including 40%-70% Cr (infiltration source), 20%-50% Ni (infiltration source), 0%-5% Pt (modifier), 0%-5% Ti (modifier) and 1%-5% NH4Cl (activator), wherein the Cr, Ni, Pt, and Ti powders are all sieved through a 1000 mesh screen to keep the total percentage of all solid phase components at 100%. The weighed solid phase components are placed in a planetary ball mill at 350rpm-400rpm for 12h-24h to obtain a uniformly mixed powder, which is the solid phase cladding powder. Subsequently, ethyl acetate (binder) is added at a ratio of 10%-30% of the mass of the solid phase components, and after being fully mixed and stirred for 2h-4h, it is placed in a planetary ball mill at 350rpm-400rpm for 8h-12h. After completion, a uniformly mixed slurry is obtained, which is the cladding slurry.
[0027] Step 2, take out the workpiece to be plated, use a high-pressure water gun to clean the surface for 5min-10min to remove oil stains, dust, etc. on the workpiece surface and remove the oxide skin, and rinse it with alcohol or acetone to provide a neat and metallic surface for subsequent slurry spraying. Subsequently, preheat the workpiece at 200℃-250℃ for 30min-60min, spray the slurry to the appropriate thickness at one time, and do not spray it in layers multiple times. Keep the spray layer thickness at 1mm-5mm and the coating coverage rate at least 98%. If the slurry layer is too thin, it will not provide sufficient penetration source, and if it is too thick, it will easily crack and peel off, affecting the uniformity of the penetration layer thickness. After spraying, let the workpiece air dry naturally for 24h-48h, and then cure it at 300℃-450℃ for 24h-48h. The segmented slurry curing process of natural air drying combined with medium and low temperature curing effectively avoids the microcracks and tiny holes caused by thermal stress in the spray layer during direct drying, and enhances the bonding strength between the slurry layer and the workpiece surface.
[0028] Step 3: The laser cladding process is as follows: laser power is 2KW-2.8KW, scanning rate is 20mm / s-40mm / s, spot diameter is 3mm-5mm, workpiece rotation speed is 3r / min-6r / min, Ar gas flow is 15L / min-20L / min. After completion, cool to room temperature and flush the surface residue of the workpiece with a high-pressure water gun or high-pressure air flow.
[0029] Through the above-mentioned processes and steps, a co-modification method for chromium-nickel cladding coatings according to the embodiment of the present disclosure is used to prepare a chromium-nickel cladding coating with a thickness of 0.85mm-1.45mm and good metallurgical bonding under the conditions of adjusting the main process parameters such as the content of solid phase components, the content of modified elements added, and laser cladding parameters. The chromium-nickel cladding coating obtained in the embodiment of the present disclosure has an oxidation corrosion resistance of 19 to 65 times higher than that of the parent material in a 600°C pure water vapor environment, and an oxidation corrosion resistance of 20 to 78 times higher than that of the parent material in a 650°C pure water vapor environment, which can be explained that the chromium-nickel cladding coating prepared by the method of the embodiment of the present disclosure effectively improves the oxidation corrosion resistance of the alloy parent material in a water vapor environment.
[0030] Example 1
[0031] Step 1: Weigh the solid phase components according to the mass ratio, including 40% Cr, 50% Ni, 4% Pt, 4% Ti and 2% NH4Cl, and place them in a planetary ball mill at 400 rpm for 12 hours to obtain solid phase cladding powder. Subsequently, add 10% ethyl acetate and stir well for 4 hours, then place it in a planetary ball mill at 400 rpm for 12 hours, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.
[0032] Step 2: Use a high-pressure water gun to clean the workpiece surface for 5 minutes, and rinse it with alcohol or acetone. Then, preheat the workpiece at 250℃ for 45 minutes, and use spraying to pre-set the slurry layer thickness to 3mm, keeping the coating coverage rate not less than 98%. Then, air dry the workpiece naturally for 48 hours and cure it at 450℃ for 48 hours.
[0033] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2KW, a scanning rate of 40mm / s, a spot diameter of 5mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 20L / min. After completion, cool to room temperature and flush the surface residue of the workpiece with high-pressure airflow. Figure 1 The dotted area in the middle is a schematic diagram of the cross-sectional morphology of the chromium-nickel cladding coating obtained in Example 1 of the present disclosure, for reference.
[0034] The processes of Examples 2 to 9 are the same as those of Example 1. Examples 1 to 9 maintain the same solid phase components and liquid phase binder ratio. The specific laser cladding process conditions are detailed in Table 1. Table 1 is the specific parameters of Examples 1 to 9 of the method for improving the corrosion resistance of the chromium-nickel cladding coating. According to the preparation steps in the above Example 1 and the specific preparation parameters in the table, chromium-nickel cladding coatings of different thicknesses and Cr atomic contents can be obtained.
[0035] Table 1
[0036]
[0037] By analyzing and studying the above examples, the thickness of the infiltration layer is measured to be about 0.85 mm-1.45 mm. The specific results are shown in Table 1. The cross-sectional morphology of the infiltration layer is as follows: Figure 1 Combining Table 1 and the cross-sectional morphology, it is found that the infiltration layer has a uniform structure, moderate thickness, sufficient diffusion of Cr atoms, and a good metallurgical bond between the infiltration layer and the matrix, which is not easy to fall off.
[0038] Example 10
[0039] Step 1: Weigh the solid phase components according to the mass ratio, including 70% Cr, 20% Ni, 5% Pt and 5% NH4Cl, and place them in a planetary ball mill at 350rpm for 24h to obtain solid phase cladding powder. Then, add 30% ethyl acetate and stir well for 2h, then place it in a planetary ball mill at 400rpm for 12h, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.
[0040] Step 2: Use a high-pressure water gun to clean the workpiece surface for 5 minutes, and rinse it with alcohol or acetone. Then, preheat the workpiece at 200℃ for 60 minutes, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%. Then, air dry the workpiece naturally for 24 hours and cure it at 300℃ for 48 hours.
[0041] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.5KW, a scanning rate of 20mm / s, a spot diameter of 2mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 15L / min. After completion, cool to room temperature and flush the surface residue of the workpiece with high-pressure airflow.
[0042] Embodiment 11
[0043] Step 1: Weigh the solid phase components according to the mass ratio, including 40% Cr, 50% Ni, 5% Ti and 5% NH4Cl, and place them in a planetary ball mill at 400 rpm for 24 hours to obtain solid phase cladding powder. Subsequently, add 20% ethyl acetate and stir well for 2 hours, then place it in a planetary ball mill at 350 rpm for 8 hours, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.
[0044] Step 2: Use a high-pressure water gun to clean the workpiece surface for 5 minutes, and rinse it with alcohol or acetone. Then, preheat the workpiece at 250℃ for 30 minutes, and use spraying to pre-set the slurry layer thickness to 2mm, keeping the coating coverage rate not less than 98%. Then, air dry the workpiece naturally for 24 hours and cure it at 450℃ for 48 hours.
[0045] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 40mm / s, a spot diameter of 3mm, a workpiece rotation speed of 2r / min, and an Ar gas flow rate of 15L / min. After completion, cool to room temperature and flush the surface residue of the workpiece with high-pressure airflow.
[0046] Example 12
[0047] Step 1: Weigh the solid phase components according to the mass ratio, including 60% Cr, 25% Ni, 5% Pt, 5% Ti and 5% NH4Cl, and place them in a planetary ball mill at 400 rpm for 12 hours to obtain solid phase cladding powder. Subsequently, add 20% ethyl acetate and stir well for 2 hours, then place it in a planetary ball mill at 350 rpm for 12 hours, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.
[0048] Step 2: Use a high-pressure water gun to clean the workpiece surface for 5 minutes, and rinse it with alcohol or acetone. Then, preheat the workpiece at 200℃ for 60 minutes, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%. Then, air dry the workpiece naturally for 24 hours and cure it at 400℃ for 48 hours.
[0049] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 20mm / s, a spot diameter of 3mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 15L / min. After completion, cool to room temperature and flush the surface residue of the workpiece with high-pressure airflow.
[0050] Embodiment 13
[0051] Step 1: Weigh the solid phase components according to the mass ratio, including 55% Cr, 32% Ni, 3% Pt, 4% Ti and 6% NH4Cl, and place them in a planetary ball mill at 400 rpm for 24 hours to obtain solid phase cladding powder. Subsequently, add 30% ethyl acetate and stir well for 2 hours, then place it in a planetary ball mill at 400 rpm for 12 hours, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.
[0052] Step 2: Use a high-pressure water gun to clean the workpiece surface for 5 minutes, and rinse it with alcohol or acetone. Then, preheat the workpiece at 250℃ for 45 minutes, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%. Then, air dry the workpiece naturally for 24 hours and cure it at 450℃ for 48 hours.
[0053] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2KW, a scanning rate of 30mm / s, a spot diameter of 5mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 18L / min. After completion, cool to room temperature and flush the surface residue of the workpiece with high-pressure airflow.
[0054] Embodiment 14
[0055] Step 1: Weigh the solid phase components according to the mass ratio, including 40% Cr, 50% Ni, 4% Pt, 4% Ti and 2% NH4Cl, and place them in a planetary ball mill at 350rpm for 12h to obtain solid phase cladding powder. Then, add 30% ethyl acetate and stir well for 4h, then place it in a planetary ball mill at 400rpm for 8h, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.
[0056] Step 2: Use a high-pressure water gun to clean the workpiece surface for 5 minutes, and rinse it with alcohol or acetone. Then, preheat the workpiece at 250℃ for 60 minutes, and use spraying to pre-set the slurry layer thickness to 4mm, keeping the coating coverage rate not less than 98%. Then, air dry the workpiece for 36 hours and cure it at 450℃ for 48 hours.
[0057] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 40mm / s, a spot diameter of 5mm, a workpiece rotation speed of 4r / min, and an Ar gas flow rate of 20L / min. After completion, cool to room temperature and flush the surface residue of the workpiece with high-pressure airflow.
[0058] Embodiment 15
[0059] Step 1: Weigh the solid phase components according to the mass ratio, including 65% Cr, 25% Ni, 2% Pt, 4% Ti and 4% NH4Cl, and place them in a planetary ball mill at 350rpm for 24h to obtain solid phase cladding powder. Then, add 20% ethyl acetate and stir well for 4h, then place it in a planetary ball mill at 400rpm for 8h, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.
[0060] Step 2: Use a high-pressure water gun to clean the workpiece surface for 5 minutes, and rinse it with alcohol or acetone. Then, preheat the workpiece at 250℃ for 60 minutes, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%. Then, air dry the workpiece naturally for 48 hours and cure it at 450℃ for 48 hours.
[0061] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 40mm / s, a spot diameter of 4mm, a workpiece rotation speed of 4r / min, and an Ar gas flow rate of 15L / min. After completion, cool to room temperature and flush the surface residue of the workpiece with high-pressure airflow.
[0062] Example 16
[0063] Step 1: Weigh the solid phase components according to the mass ratio, including 55% Cr, 35% Ni, 4% Pt, 2% Ti and 4% NH4Cl, and place them in a planetary ball mill at 400 rpm for 24 hours to obtain solid phase cladding powder. Subsequently, add 30% ethyl acetate and stir well for 4 hours, then place it in a planetary ball mill at 400 rpm for 8 hours, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.
[0064] Step 2: Use a high-pressure water gun to clean the workpiece surface for 5 minutes, and rinse it with alcohol or acetone. Then, preheat the workpiece at 250℃ for 60 minutes, and use spraying to pre-set the slurry layer thickness to 5mm, keeping the coating coverage rate not less than 98%. Then, air dry the workpiece naturally for 24 hours and cure it at 450℃ for 48 hours.
[0065] Step 3: Place the workpiece under Ar for laser cladding, with a laser power of 2.8KW, a scanning rate of 35mm / s, a spot diameter of 4mm, a workpiece rotation speed of 2r / min, and an Ar gas flow rate of 18L / min. After completion, cool to room temperature and flush the surface residue of the workpiece with high-pressure airflow.
[0066] The co-modification method for chromium-nickel cladding coatings disclosed in the embodiments of the present invention is suitable for austenitic steel and high-temperature alloy components used in large boilers, oil and gas field transportation pipelines and other workpieces with large aspect ratios and various complex shapes. It has strong practicality, high permeation rate, excellent membrane-base bonding, and extremely good industrial mass production benefits.
[0067] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.
Claims
1. A co-modification method for chromium-nickel cladding coating, characterized in that: The following steps are involved: Step 1, weigh and prepare solid-phase cladding powder and liquid-phase binder in proportion, and prepare cladding slurries of different proportions after stirring and ball milling for use; Step 2: Clean and preheat the surface of the workpiece to be plated, then spray the cladding slurry evenly onto the workpiece surface, and dry and solidify after spraying; Step 3: placing the workpiece after the spray coating is solidified in an inert atmosphere for laser cladding, obtaining a chromium cladding coating after cooling, and performing cladding residue treatment.
2. A co-modification method for chromium-nickel cladding coating according to claim 1, characterized in that: In step 1, the infiltration sources are Cr and Ni powders, the modifiers are Pt and Ti powders, the activator is NH4Cl, and the binder is ethyl acetate; wherein the Cr, Ni, Pt, and Ti powders are all sieved through a 1000-mesh sieve.
3. A co-modification method for chromium-nickel cladding coating according to claim 1, characterized in that: In step 1, the preparation method of solid phase cladding powder is as follows: solid phase components are weighed according to mass percentage, including 40%-70% Cr, 20%-50% Ni, 0%-5% Pt, 0%-5% Ti and 1%-5% NH4Cl, and the total mass of the solid phase components is maintained at 100%. After weighing, they are mixed by ball milling in a planetary ball mill, and the ball milling speed is 350rpm-400rpm and the time is 12h-24h.
4. A co-modification method for chromium-nickel cladding coating according to claim 1, characterized in that: In step 1, the cladding slurry preparation method is as follows: the binder ethyl acetate is added to the uniformly mixed solid phase powder at a mass ratio of 10%-30% of the solid phase component, and after being fully stirred for 2h-4h, it is placed in a planetary ball mill for ball milling mixing. The ball milling speed is 350rpm-400rpm and the time is 8h-12h.
5. A co-modification method for chromium-nickel cladding coating according to claim 1, characterized in that: In step 2, the preheating treatment is medium frequency preheating at 200°C-250°C for 30min-60min.
6. A co-modification method for chromium-nickel cladding coating according to claim 1, characterized in that: In step 2, the prefabricated slurry layer has a thickness of 1 mm to 5 mm and a coating coverage of not less than 98%.
7. A co-modification method for chromium-nickel cladding coating according to claim 1, characterized in that: In step 2, the pre-coating is dried by natural air drying for 24h-48h, and cured at 300°C-450°C for 24h-48h.
8. A co-modification method for chromium-nickel cladding coating according to claim 1, characterized in that: In step 3, the laser power is 2KW-2.8KW, the scanning rate is 20mm / s-40mm / s, the spot diameter is 3mm-5mm, the workpiece rotation speed is 3r / min-6r / min, and the Ar gas flow rate is 15L / min-20L / min.